A HYPERTENSIVE RESPONSE TO EXERCISE IS ASSOCIATED WITH ALTERED CARDIAC STRUCTURE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (April 2021) - Moore, Myles; Climie, Rachel; Otahal, Petr; Sharman, James; Schultz, Martin
Abstract : Objective: A hypertensive response to exercise (HRE) is a risk factor for cardiovascular disease and may reveal high blood pressure (BP) not detected by standard assessment at rest. Structural cardiac disease may underlie the association between HRE and cardiovascular risk, although this has not been fully elucidated. This study aimed to assess the relationship between HRE and cardiac structure via systematic review and meta-analysis of previously published literature. Design and method: Three online databases were searched from inception to July 2019 for studies that included associations between exercise BP and cardiac structural variables including left ventricular mass index (LVMI), relative wall thickness (RWT) and left atrial (LA) diameter. Pooled correlations between exercise BP and cardiac variables were calculated using random effects. Pooled mean differences (random effects) in LVMI, RWT and LA size between individuals with and without HRE were also calculated. Univariable meta-regressions were performed to assess differences in pooled mean differences by resting hypertension status, health status, exercise intensity at the time BP was measured and exercise modality. Results: A total of 47 studies with 23, 090 participants (aged 44 ± 4 years; 62% male) were included. Exercise systolic BP had a moderate association with LVMI (22 studies, pooled r = 0.4, p < 0.001) and RWT (3 studies, r = 0.4, p < 0.001). On average, those with HRE had higher LVMI (24 studies, pooled mean difference 9.34 ± 1.7 g/m2; p < 0.001), RWT (13 studies, 0.02 ± 0.004, p < 0.001) and LA diameter (10 studies, 1.97 ± 0.49 mm, p < 0.001) compared to those without HRE. Meta-regression for pooled mean difference in LVMI indicated results were similar irrespective of resting hypertension status, health status and exercise intensity at BP measurement, but was greater among studies using treadmill testing (n = 18) compared to cycling (n = 6, p = 0.003). Meta-regression for pooled mean difference in RWT were similar irrespective of resting hypertension status, health status and test modality, but were greater during submaximal compared to peak intensity exercise (p = 0.02). Conclusions: HRE is associated with altered cardiac structure, including increased LVMI, RWT and LA diameter. Whilst associations varied across exercise intensity and testing modality, these results highlight potential mechanisms underlying cardiovascular risk associated with HRE.